'Turn On/Off' fluorescence probe for the screening of unactivated Bruton's tyrosine kinase. Issue 10 (15th May 2015) - Kawahata, Wataru; Asami, Tokiko; Fujii, Ikuo; Sawa, Masaaki
Graphical abstract: Abstract: BTK has emerged as a promising target for treating B-cell malignancies and autoimmune diseases, and there has been a growing demand to identify selective BTK inhibitors efficiently. In this Letter, we have designed and synthesized a new fluorescent probe to screen compounds that preferentially bind to an unactivated state of BTK (BTK [U]). The fluorescence of the probe was turned on in the presence of BTK [U], and quenched by the addition of compounds which preferentially bind to BTK [U]. This unique fluorescent probe was successfully applied to the screening of a kinase focused compound library. The results suggest that this new method is a simple and easy-to-perform assay to screen inhibitors of BTK [U].